Efektifitas Kalender Pendidikan pada Mata Pelajaran PAI terhadap Kurikulum Merdeka Belajar: Studi di SMAN 9 Kota Malang - Hanum Mir'atul Maslahah; Muhammad Wahyudi Hanggara; Muhammad Mukhtar Zaidan Katong; Sutiah (Realita: Jurnal Penelitian dan Kebudayaan Islam, 2024)
The aim of this research is to describe the effectiveness of an academic calendar based on the independent learning curriculum which has a different structure from the previous curriculum, K-13. Apart from that, it also explains the efficiency of implementing the academic calendar based on the independent learning curriculum. The research method is a descriptive qualitative method with data collection including interviews, observation and documentation. The research results show that differences in curriculum have resulted in changes in the composition of the educational calendar. So that schools can implement this, they need time to adapt, make transitions, measure effectiveness and efficiency and evaluate the implementation of the educational calendar in the independent curriculum.